Childhood, Youth, and Identity: A Roundtable Conversation from the Global South - Kannan, Divya; Dar, Anandini; Duff, Sarah E.; Sen, Hia; Nag, Shivani; Bergère, Clovis (Journal of Childhood Studies, 2022)
This roundtable session initially took place as part of the international conference “Childhood, Youth, and Identity in South Asia,” organized by the Department of History, Shiv Nadar University, Greater Noida, and the Centre for Publishing, Ambedkar University Delhi, India, on January 6–7, 2020.